Backwards Asymptotically Autonomous Dynamics for 2D MHD Equations - Jiali Yu; Wenhuo Su; Dongmei Xu (Discrete Dynamics in Nature and Society)
We consider the backwards topological property of pullback attractors for the nonautonomous MHD equations. Under some backwards assumptions of the nonautonomous force, it is shown that the theoretical existence result for such an attractor is derived from an increasing, bounded pullback absorbing and the backwards pullback flattening property. Meanwhile, some abstract results on the convergence of nonautonomous pullback attractors in asymptotically autonomous problems are established and applied to MHD equations.